(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article presents the results of analyzes carried out with different chemical compounds, which significantly slows down the harmful effect of oxygen under thermal decomposition of polyvinyl chloride. Comprehensive studies have shown that gossypol is a strong inhibitor of free radical oxidation and surpasses in efficiency many known synthetic inhibitors.